2019
DOI: 10.1093/humupd/dmz038
|View full text |Cite
|
Sign up to set email alerts
|

Age-related presence of spermatogonia in patients with Klinefelter syndrome: a systematic review and meta-analysis

Abstract: BACKGROUND Klinefelter syndrome (KS) has been defined by sex chromosome aneuploidies (classically 47, XXY) in the male patient. The peripubertal timeframe in KS patients has been associated with the initiation of progressive testicular fibrosis, loss of spermatogonial stem cells (SSC), hypogonadism and impaired fertility. Less than half of KS patients are positive for spermatozoa in the ejaculate or testis via semen analysis or testicular sperm extraction, respectively. However, the chance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 75 publications
0
41
1
3
Order By: Relevance
“…Pure 45,X monosomy is associated with a more severe phenotype of severe short stature, gonadal dysgenesis, and dysmorphic features compared to mosaic genotypes who may enter puberty spontaneously before developing primary ovarian failure, premature loss of oocytes, and infertility. Klinefelter syndrome is characterized by the presence of a 47,XXY cell line and clinical features include tall stature, small testes, gynecomastia, primary gonadal failure, progressive germ cell loss, and infertility [20]. 46,XX/46,XY mosaicism and 46,XX/46,XY chimerism are associated with dysgenetic gonads, infertility, and a highly variable phenotype which may present with ambiguous genitalia at birth [21].…”
Section: Disorders Of Sex Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure 45,X monosomy is associated with a more severe phenotype of severe short stature, gonadal dysgenesis, and dysmorphic features compared to mosaic genotypes who may enter puberty spontaneously before developing primary ovarian failure, premature loss of oocytes, and infertility. Klinefelter syndrome is characterized by the presence of a 47,XXY cell line and clinical features include tall stature, small testes, gynecomastia, primary gonadal failure, progressive germ cell loss, and infertility [20]. 46,XX/46,XY mosaicism and 46,XX/46,XY chimerism are associated with dysgenetic gonads, infertility, and a highly variable phenotype which may present with ambiguous genitalia at birth [21].…”
Section: Disorders Of Sex Developmentmentioning
confidence: 99%
“…The testicular phenotype of KS involves a progressive loss of spermatogonial stem cells (SSC) beginning in prepuberty, with testicular fibrosis occurring in (peri)pubertal and adult patients [135]. A meta-analysis of the presence of spermatogonia in individuals with KS demonstrated spermatogonia in the testes of all fetal/infantile samples, 83% of those obtained from prepubertal patients, and in 40-50% of adolescent/adult individuals [20].…”
Section: Klinefelter Syndromementioning
confidence: 99%
“…Van Saen et al [69] reported that there is a progressive loss of spermatogonial stem cells that begins at prepubertal time, with frequent testicular fibrosis by adulthood. A meta-analysis of the presence of spermatogonia in individuals with KS demonstrated their presence in the testes of all fetal/infant samples, in 83% of those obtained from prepubertal patients, and in 40-50% of adolescents/adults [70]. Thus, the options for fertility preservation in individuals with KS depend on the age of the patient.…”
Section: Klinefelter Syndrome (Ks)mentioning
confidence: 99%
“…It is still debated whether the chances to find foci within the testes with remnant intact spermatogenesis decrease with advancing age in KS [132][133][134]. Fertility in KS may also be linked to their Leydig cell functionality 106.…”
mentioning
confidence: 99%